PERGESERAN NILAI MORAL DALAM MEME "KIDS JAMAN NOW" - Noveria Anggraeni Fiaji (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
This paper will examine the shift in the values / character of children of today's "kids zaman now" with the ancient children "kids zaman old" through memes that have been widely circulated in social media. Each meme contains a discourse that compares between generations past and present. From the proposition will be seen, assessed, and compared based on the positive and negative elements of the moral message presented. The results obtained from both propositions explain that the shift in moral values occurs significantly between generations past and present. Negative moral elements always lie in the proposition of "kids of the times" and positive elements are always emphasized on "kids age old". Of the many memes used as data, one of the factors that led to the shift in moral values is modern technology (gawai).